Review of geology of Kansas - Bain, Alvah I. (My University, 1900)
Introduction: General description of the state. The state of Kansas lies between 49 38 and 102 W longitude and 37 and 40 N latitude, and has an extent of about 400 miles in length, and 200 miles in breadth, embracing an area of about 32,060 square miles, or 52,572,160 acres. Its average altitude is out 2,375 feet above sea level. The large streams flow to the south and east, with a gradual fall of about even to eight feet per mile. Nowhere in the state can there be found a water fall of any great height. The principal rivers are: the Kansas or Kaw, Arkansas, Solomon, Republican, Big Blue, Smoky Hill, Saline and Virdigris. Kansas has no mountains. Between the river valleys, which are formed by erosion, the surface is that of a gentle, rolling prairie with a few steep hills and bluffs. The soil of the state, both prairie and bottom, is the same fine, black, rich, loam, and only differs in thickness. General stratification & origin of strata. By Stratified rocks, we mean rocks which are formed in successive layers, of the same or different kinds of materials, and varying greatly in thickness, depending upon the amount of material deposited at the time of the formation. Stratified rocks are generally deposited under water. We all have noticed the weathering and wearing away of our soils, and the materials carried away to the sea by our rivers. If we could examine a section taken from the bottom of the sea, especially shallow parts of the sea near the coast, we should find that the materials are formed in this stratified condition. In the different layers, would be found materials of different kinds. It is quite easy for us to see how these different materials came to be there. All of our great rivers passing through the country gathered all sorts of materials from the different rocks over which they passed and carried them to the sea; and here, as the current slackened, these particles gradually settled to the bottom, and formed this great mass of materials.
Citation: Bain, Alvah I. Review of geology of Kansas. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Geology; Kansas; Limestone; Shale; Rocks; Theses